2022
DOI: 10.3389/fpsyg.2022.833847
|View full text |Cite
|
Sign up to set email alerts
|

Does It Pay to Issue Green? An Institutional Comparison of Mainland China and Hong Kong’s Stock Markets Toward Green Bonds

Abstract: The stock market is an indicator of investor sentiment when it comes to new information or innovative firm-level products. Green bonds are both innovative and unique in terms of their higher information disclosures and understanding the impact of sustainable finance on investor outlook for a company’s stock. Using the comparative case of Mainland China and Hong Kong’s stock market, we examine whether green bond announcements from 2016 to 2019 can create significant investor reactions. By employing the event st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Further, research on the relationship between climate change, economic aspects, and risk management was notable (Stern 2022;Wright et al 2015;Rocha et al 2022;Tripathy 2017). 'Sustainable development', 'financial markets', 'green investment', 'green innovation', 'corporate social responsibility', 'environmental regulation', and 'China' words were also striking (Purkayastha and Sarkar 2021;Dong et al 2022;Chen et al 2022;Chi et al 2023;Huang and Lei 2021). The interdependence of green bonds and other financial markets, including the stock market, carbon, and conventional financial markets, has garnered attention, majorly in China (Ren et al 2022;Jiang et al 2022a;Su et al 2022;Naeem et al 2021;Elsayed et al 2022;Verma and Bansal 2023;Xi and Jing 2022;Mensi et al 2022).…”
Section: Word Cloudmentioning
confidence: 99%
“…Further, research on the relationship between climate change, economic aspects, and risk management was notable (Stern 2022;Wright et al 2015;Rocha et al 2022;Tripathy 2017). 'Sustainable development', 'financial markets', 'green investment', 'green innovation', 'corporate social responsibility', 'environmental regulation', and 'China' words were also striking (Purkayastha and Sarkar 2021;Dong et al 2022;Chen et al 2022;Chi et al 2023;Huang and Lei 2021). The interdependence of green bonds and other financial markets, including the stock market, carbon, and conventional financial markets, has garnered attention, majorly in China (Ren et al 2022;Jiang et al 2022a;Su et al 2022;Naeem et al 2021;Elsayed et al 2022;Verma and Bansal 2023;Xi and Jing 2022;Mensi et al 2022).…”
Section: Word Cloudmentioning
confidence: 99%
“…Gao, Li, and Wang (2023) investigate the influence of investor attention on green security markets, including green bonds and green stocks in China, and show that green stocks and investor attention are more interdependent than green bonds. Chen, Weber, and Saravade (2022) investigate the general investor reaction to green bond announcements in the stock markets of Mainland China and Hong Kong and discover that both stock markets react positively to green bond announcements, indicating that investor reaction is favorable.…”
Section: Empirical Literature On the Relationship Between Investor At...mentioning
confidence: 99%
“…On the other hand, research has shown that green bonds can positively affect corporate financial performance and stock prices [22]. Companies that issue them may experience an increase in the price of their stocks following the issuance announcement, indicating that investors perceive green bonds as a positive signal of the company's commitment to sustainability [23].…”
Section: Literature Reviewmentioning
confidence: 99%